The status of mitochondrial apparatus in rat atrial contractive cardiomyocites under the acute myocardial ischemia. - Dunaev A.V. (Морфологія, 2007)
The purpose of the study was to analyze morphological reactions of mitochondrial apparatus of atrial contractive cardiomyocites in rats on the acute myocardial ischemia. Modeling of the acute myocardial ischemia in rats was realized by daily introduction of vasopressin intraperitoneum in dosage 1 Ed of rat weight. Morphological research comprised both light and electronic microscopy of myocardium of right and left atria, right and left auricles, and also interatrial septum. Stereological estimation of several indexes was carried out: the compactness of mitochondria, numeral compactness of mitohondria, surface area of external mitochondrial membrane, compactness of mitochondrial cristae, number of mitochon-drial cristae, surface area of internal mitochondrial membrane, degree of cristae orientation, coefficient of mitochondrial sphericity, volume of mitochondrium, quantitative correlation of types of mitochondria. It was shown that the reaction of different types of mitochondria on development of acute myocardial ischemia in atrial contractive cardiomyocites depends on the structural-metabolic type of mitochondria. Under the acute myocardial ischemia the moderate diffuse reduction of mitochondrial apparatus of contractive cardiomyocites takes place that is accompanied by the prolonged renewal of high-energy mitochondria and causes energetical limitation of contractive function of atrial myocardium.